2005
DOI: 10.2337/diabetes.54.9.2734
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide 1 Regulates Sequential and Compound Exocytosis in Pancreatic Islet β-Cells

Abstract: Glucagon-like peptide 1 (GLP-1) has been postulated to potentiate insulin secretion by cAMP-mediated enhancement of mobilization and priming of secretory granules, but the precise exocytic events are unknown. We used epi-fluorescent microscopy of the fluorescent dye FM1-43, which incorporates into the plasma membrane and the exocytosing secretory granules (appearing as plasma membrane hotspots). KCl evoked exocytosis of 1.8 ؎ 0.5 hotspots/rat ␤-cell at the cell periphery, 82% of which are single transient incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 35 publications
7
77
0
Order By: Relevance
“…More frequently, fused chain of insulin granules were observed in the primary beta cells ( Fig. 2A, arrow), similar to previous reports (Kwan and Gaisano, 2005;Hoppa et al, 2012). They collapse into the plasma membrane and release insulin in a multiple-granular manner ( Fig.…”
Section: Flash Photolysis and Depolarization Can Elicit Clathrinindepsupporting
confidence: 90%
See 1 more Smart Citation
“…More frequently, fused chain of insulin granules were observed in the primary beta cells ( Fig. 2A, arrow), similar to previous reports (Kwan and Gaisano, 2005;Hoppa et al, 2012). They collapse into the plasma membrane and release insulin in a multiple-granular manner ( Fig.…”
Section: Flash Photolysis and Depolarization Can Elicit Clathrinindepsupporting
confidence: 90%
“…Moreover, the intermediate organelle generated by bulk-like endocytosis is proposed to be incapable of efficiently generating fusion-competent synaptic vesicles (Hayashi et al, 2008;Heerssen et al, 2008). However, compound exocytosis of prefused insulin granules was reported in rat pancreatic beta cells in 2005 (Kwan and Gaisano, 2005). Recently, compound exocytosis has been further demonstrated to play a important role under conditions associated with the global elevation of cytosolic Ca 2+ (Hoppa et al, 2012), which is the condition that augments the bulk-like endocytosis found in the present study.…”
Section: Disscusionsupporting
confidence: 40%
“…Electron microscopy Islets were fixed and sections were examined and photographed with a Hitachi H-7000 transmission electron microscopy (EM) system as described previously [8]. Please refer to the ESM Methods for further details.…”
Section: Methodsmentioning
confidence: 99%
“…The roles of SYN-2 and SYN-3 in insulin secretion are unknown. As SYN-3 appears to be the only SYN localised to SGs, we can surmise that SYN-3 possibly influences newcomer SG fusion and/or SG-SG fusion [3,8,13]. We thus proceeded to examine this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation